(3RgQI Gdebhd aj fSH KGfj aQYj GdQShds - (3GdMeRj, Rjf GdOjf, GHf TObe, Ydj Hf GdMSf Hf TObe GdMeRj, J (B1033(3g` (B1624(3es
(3ChdgG (B:s
(3ChdgG(B: (3MeOG dhdj GdEMSGf hGdfYe (B... (3ajgG KdGK ebOeGJ heWdH hNGJeI, GdebOeI GdChdi cd eG GPcQg aj gPg GdQSGdI aEfeG gh Yf cJGH hGdPj GdePchQs
(3BNQgG (B:s
(3BNQgG(B: (3bO hUdJ gfG aj GdRgQI HYV GdSdGSd HCUdgG hde jUdgG hGdOj QMeg Gddg hPdc GdhUd YhdJ aj HYVg Ydi NHQ TQYj hKHJ Hg GdfSH, haj GdHGbj Ydi NHQ CaGOfj GdXf hs
(3GdfSNI efbhdI Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 275s
(3GdPQjYI, L (B12: 55s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs